Inductive teaching approaches in business English writing in an EFL context: Paper-based and product-based instructions - Piyawan Rungwaraphong (Universitas Ahmad Dahlan, 2021)
The study reported in this article compared two different inductive instructional methods implemented in a Business English writing training, including paper-based instruction (PPI) and product-based instruction (PDI). It assessed the effectiveness and examined practical issues of the implementation of each method. A total of 46 Thai students majoring Business English program in a Thai university took part in this study. The students were randomly divided into two groups and put into either PPI or PDI training module. Data were collected from direct observations, focused-group discussions, and students’ writing scores. Qualitative data from the focused-group discussions and observation field notes were analyzed thematically using the grounded theory while students’ writing scores were cross-examined. Results of the study indicate that the fundamental dichotomies between both approaches include the tangibility, authenticity and contextuality. Students’ difficulties in formulating grammar and rules in writing on their own, and students’ perception of learning as a burden were found as the challenges occurred in both modules. The findings also indicate that both PPI and PDI modules trigger the dynamics and positive atmosphere; however, PDI resulted in more vigorous dynamics as student movements and interactions were relatively higher. Finally The findings of this study are beneficial instructors who are seeking innovative instructional methodology to improve their teaching of business English writing. Based on the findings of this study, PDI will enable instructors to create chances for students to learn in authentic professional environments, contexts and culture that are casted in the real-life business situations.